Peripheral Circulations, Transient Centralities: The International Geography of the Avant-Gardes in the Interwar Period (1918–1940). (2nd October 2019) - Joyeux-Prunel, Béatrice
Abstract : This article questions the common historiography about the avant-gardes in the interwar period, in which Paris is often considered the international avant-garde capital city, with surrealism as its perfect model. It starts with the idea that the history of the avant-gardes (artists and artists' groups who considered themselves or who were considered innovative) could be studied as "a social field, " but also an international field structured by mobility. It focuses on the circulation of avant-garde artists and their works, as well as the social, economic, financial, geopolitical, and colonial bases of these circulations, to understand how some groups, artists, stories, and centers managed to establish themselves better than others. Contrary to the regular narrative based on Parisian domination, a circulatory approach highlights that Paris isolated itself from avant-gardes in the 1920s, unlike the opening of Germany and Central Europe, and that the surrealists themselves were not so international until 1929. Looking at social groups, at their movements and circulation, as well as the various strategies deployed and the underlying geopolitical positions taken by artists after 1929, it shows that from 1929, the Parisian scene, and the surrealist movement in particular, very slowly became a new focus for new artistic generations. Paris only became a global center of avant-garde circulation after 1934 and surrealism then gradually became the focus of international artists' careers. In this process, artists coming from the peripheries of Europe and the Americas, cultural transfers, and resemanticization processes played a central role.